Challenges of Small-Scale Entrepreneur’s in Sohar Port Anyone There to Listen? - P R, Brinda Kalyani.; M, Dileep Kumar; Al Maqbali, Laila (UUM Press, 2015)
Investment by its nature looks forward to the highest rate of earnings and which support the development of a country. In order to meet right investment a stable business environment is required. Sohar Industrial Port is one of the major investment and employment hubs of Oman. The emergence of SMEs in Ports of Oman paves way for higher rate of earnings and attracts lot of Entrepreneurs to set up business in the ports of Oman. As it is claimed, this investment has aimed at employment opportunities to the growing educated youngsters. Though such developments are going on, there are very less studies focused on the opportunities and challenges of SMEs in the Sohar port. Contemporarily, a study, which focuses on the challenges of entrepreneurs, that to analyze the development climate in the ports of Sultanate of OMAN, needs to be explored into. This research paper thus extends better insight into Sohar Port as employment and Investment hub of Oman: the challenges of SMEs and entrepreneurs in the “Sohar port”.